Comments, analytics, and social media : the impact of audience feedback on journalists’ market orientation - Hanusch, Folker (2021)
This study sought to empirically test whether exposure to and use of new audience feedback mechanisms have an influence on journalism culture. Specifically, the study was interested in testing whether such mechanisms impact the extent to which journalists perceive changes over time in their role conceptions. Such an exploration is timely and important. The roles journalists conceive of are shaped, in part, by what they think audiences expect from them. Such expectations are now communicated to journalists routinely and easily through new audience feedback mechanisms: reader comments, social media, and web analytics. Based on an online survey of 358 news journalists in Australia, this study found that reading readers’ comments frequently is related to an increase in the perceived importance of both consumer and citizen orientations. In contrast, perceived effectiveness of web analytics as audience feedback is related to an increase in the perceived importance of consumer orientation.